2012
DOI: 10.1073/pnas.1118710109
|View full text |Cite
|
Sign up to set email alerts
|

Transcription from the second heavy-strand promoter of human mtDNA is repressed by transcription factor A in vitro

Abstract: Cell-based studies support the existence of two promoters on the heavy strand of mtDNA: heavy-strand promoter 1 (HSP1) and HSP2. However, transcription from HSP2 has been reported only once in a cell-free system, and never when recombinant proteins have been used. Here, we document transcription from HSP2 using an in vitro system of defined composition. An oligonucleotide template representing positions 596-685 of mtDNA was sufficient to observe transcription by the human mtRNA polymerase (POLRMT) that was abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 35 publications
5
66
0
2
Order By: Relevance
“…There is no consensus on whether the HSP2 promoter exists. Some reports have failed to observe initiation from HSP2 in reconstituted transcription systems, whereas others have suggested that transcription initiation at HSP2 can be observed in vitro (30,(56)(57)(58)(59). However, the data are not congruent because the precise HSP2 transcription start site mapped in vitro differs from the one that has been mapped in vivo (55,59).…”
Section: Mitochondrial Transcription Termination Factormentioning
confidence: 59%
“…There is no consensus on whether the HSP2 promoter exists. Some reports have failed to observe initiation from HSP2 in reconstituted transcription systems, whereas others have suggested that transcription initiation at HSP2 can be observed in vitro (30,(56)(57)(58)(59). However, the data are not congruent because the precise HSP2 transcription start site mapped in vitro differs from the one that has been mapped in vivo (55,59).…”
Section: Mitochondrial Transcription Termination Factormentioning
confidence: 59%
“…inhibited by TFAM [12,13]. These recent observations suggest far more regulation of mitochondrial transcription than previously imagined.…”
Section: Accepted Manuscriptmentioning
confidence: 79%
“…PGC-1␣ is a key transcriptional regulator of cellular energy metabolism to stimulate mitochondrial biogenesis (3). TFAM is capable of binding and wrapping mtDNA, as well as activating and regulating mtDNA transcription and replication (8,30,37). TFAM plays a key role in mitochondrial biogenesis, since it is essential to the initiation of both the replication and expression of mtDNA, which encodes portions of the mitochondrial proteins, such as cytochrome c oxidase II (13).…”
Section: Discussionmentioning
confidence: 99%